Frequency and Determinants of Erectile Dysfunction in Maintenance Haemodialysis Patients - Fazl E Mateen, Shahzad Shokat, Syed Muhammad Hassan Akhtar, Muhammad Shahzad Hafeez, Qaswer Saeed (Pakistan Journal of Medical & Health Sciences, 2023)
Background: End-Stage Renal Disease (ESRD) requires lifelong hemodialysis and increases the risk of complications like cardiovascular issues, depression, infections, and sleep disorders. Erectile dysfunction (ED), though often underreported due to stigma, is highly prevalent affecting up to 81.67% of patients, with only 8.77% showing normal function in some studies. Objective: The objective of this study was to determine the frequency of erectile dysfunction and to identify its determinants among patients undergoing hemodialysis. A cross-sectional study design was employed. Methods: The study was conducted at the Dialysis Center of Jinnah Hospital / Allama Iqbal Medical College, Lahore, from July 2022 to December 2022.Following ethical approval and informed consent, eligible patients were enrolled. Erectile dysfunction was assessed using the International Index of Erectile Function-5 (IIEF-5) Score. The determinants evaluated included age, duration of dialysis, diuresis status, serum testosterone, serum albumin, smoking status, diabetes, hypertension, peripheral neuropathy, and depression. Patient confidentiality and anonymity were strictly maintained throughout the study. Results: Among the 125 patients on hemodialysis, the mean age was 42.92 ± 16.01 years, and the mean duration of dialysis was 15.24 ± 6.77 months. The mean IIEF-5 score was 15.24 ± 7.24, indicating a significant prevalence of erectile dysfunction. The mean HbA1c level was 6.04 ± 0.82, the mean serum albumin level was 38.56 ± 9.59, and the mean serum testosterone level was 377.64 ± 204.28. Conclusion: It is concluded that patients with end stage renal disease had significant association with erectile dysfunction. Keywords: Erectile Dysfunction, Hemodialysis, End-Stage Renal Disease (ESRD), IIEF-5, Testosterone, Serum Albumin, Diabetes, Hypertension, Depression.